REALIZATION OF POLITENESS ON STUDENTS’ RESPONSIVE UTTERANCE IN CLASSROOM INTERACTION - Fitria Cahyaningrum; Andayani Andayani; Budhi Setiawan (Fakultas Bahasa dan Seni UNP, 2018)
The purpose of this study is to describe the form and function of students’ responsive speech politeness in class interaction at Senior High School. The method used is qualitative descriptive research method with sociopragmatic approach. Data were students’ speech in the process of learning Bahasa Indonesia. Technique of collecting data through recording technique with free listening method (SBLC). Data analysis technique used interactive model in the form of data collecting, data reduction, data analysis, and drawing conclusions. The results show that there is compliance with the tact maxim, generosity maxim, modesty maxim, agreement maxim, and sympathy maxim. The responsive speech acts are directive, assertive, and expressive that serve acceptance, rejection, request and praise.Keywords: form of responsive speech act, responsive speech act function, classroom interaction.REALISASI KESANTUNAN TUTURAN RESPONSIF SISWA DALAM INTERAKSI KELAS AbstrakPenelitian ini bertujuan untuk mendeskripsikan bentuk dan fungsi kesantunan tindak tutur responsif siswa dalam interaksi kelas di Sekolah Menengah Atas. Metode yang digunakan ialah metode penelitian deskriptif kualitatif dengan pendekatan sosiopragmatik. Data berupa tuturan siswa dalam proses pembelajaran Bahasa Indonesia. Teknik pengumpulan data melalui teknik perekaman dengan metode simak bebas libat cakap (SBLC). Teknik analisis data menggunakan model interaktif berupa pengumpulan data, reduksi data, analisis data, dan penarikan kesimpulan. Hasil penelitian menunjukkan terdapat pematuhan maksim kebijaksanaan, maksim kedermawanan, maksim kesederhanaan, maksim kesepakatan, dan maksim kesimpatian. Adapun tindak tutur yang ditemukan berbentuk direktif, asertif, dan ekspresif yang berfungsi menerima, menolak, meminta, dan memuji.Kata kunci: bentuk kesantunan tindak tutur responsif, fungsi tindak tutur responsif, interaksi kelas.